THE EFFECT OF WORK MOTIVATION AND SPIRITUAL INTELLIGENCE ON EMPLOYEE PERFORMANCE WITH ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) AS INTERVENING VARIABLES - Panji Dwi Herdian; Riyadi Nugroho; Sumiati Sumiati (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2020)
This research aims to analyze the effect of work motivation and spiritual intelligence on employee performance with organizational citizenship behavior as an intervening variable, was conducted on organic employees at PT. Barata Indonesia (Persero),, with a total sample of 158 employees. Data was collected by distributing questionnaires filled out by employees then analyzed using SPSS and SEM software.This study will use two kinds of analysis techniques, namely (1) Confirmatory Factor Analysis on SEM which is used to confirm the most dominant factors in one group of variables and (2) Regression Weight on SEM which is used to examine how much the relationship between variables. The results showed that the Organizational Citizenship Behavior variable had the strongest relationship with Employee Performance, with CR a value of 4.249 with a P-value <5%. which means the higher organizational citizenship behavior, the higher the employee's performance.